2020
DOI: 10.1111/ijcp.13784
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physician’s knowledge in Jordan about the ACC/AHA blood cholesterol guidelines

Abstract: Background Elevated levels of blood lipids are considered a major modifiable risk factor for the development of cardiovascular diseases. The optimal management of dyslipidaemia remains inadequate worldwide. Accordingly, there is an increasing need to evaluate the basis that health care providers are using to control dyslipidaemia. Aim To evaluate the awareness of Jordanian physicians about the American College of Cardiology/American Heart Association (ACC/AHA) guidelines for dyslipidaemia management. Method A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This is similar to a finding from Singapore in which authors found a higher familiarity with 2013 ACC/AHA guidelines among cardiologists than endocrinologists/nephrologists or the GPs [ 16 ]. Also, findings from Jordan found that physicians’ rank can play an essential role in clinicians’ knowledge [ 15 ]. Similarly, Mosca et al found that cardiologists and primary care physicians were substantially more aware of and incorporated CVD recommendations into practice than other specialties [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to a finding from Singapore in which authors found a higher familiarity with 2013 ACC/AHA guidelines among cardiologists than endocrinologists/nephrologists or the GPs [ 16 ]. Also, findings from Jordan found that physicians’ rank can play an essential role in clinicians’ knowledge [ 15 ]. Similarly, Mosca et al found that cardiologists and primary care physicians were substantially more aware of and incorporated CVD recommendations into practice than other specialties [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study’s target population consisted of 1732 physicians, according to the last annual health report of the number of physicians in Sana’a [ 17 ]. The total sample size was calculated to be 214 based on the following formula N = 4 Z α 2 S 2 ÷W 2 [ 18 ], assuming a 95% confidence interval, Z α of 1.96, W/S ratio of 0.3 [ 15 ], and 20% for non-responses or in case of incomplete questionnaires. A total of 350 questionnaires were distributed.…”
Section: Methodsmentioning
confidence: 99%
“…The gap of knowledge regarding statin intensities has been shown in previous work from Suadi Arabia, where the questions about statin monitoring and the highintensity statin group had the lowest percentage of correct answers with 9.1% and 28.6%, respectively [10]. In Jordan, more than half of the physicians were able to define the moderateand high-intensity statin groups and gave correct examples for each of them [11].…”
Section: Clinical Knowledge About Statin Therapymentioning
confidence: 94%
“…Their answers were either they do not need a statin or should receive a low-intensity dose. Rababa'h et al (2020) found that only 45.4% of participating Jordanian physicians recommended the right therapeutic statin plan for diabetic patients aged 40-75 years old [11]. Although several studies worldwide have reported the underutilization of statins among patients with DM aged 40-75 years old, in our study, we confirm the lack of knowledge among Yemeni physicians and pharmacists regarding statin use in DM patients as a potential reason for the underutilization of statins among patients for primary prevention in Yemen, particularly diabetic patients aged 40-75 years old.…”
Section: Clinical Knowledge About Statin Therapymentioning
confidence: 99%
See 1 more Smart Citation